(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The inactivation of the rat liver arginase in condition of pH 3.6 during different time periods and different ionic powers of gly–HCl buffer (0.05; 0.1 and 0.2 M) was examined. In fact, the increase of buffer molarity observes the certain increase of enzyme inactivation percent. Inactivation also depends on ionic power of tris–HCl (pH 7.4) buffer. Maximum percent of reactivation was discovered in 0.01 M of buffer tris–HCl (pH 7.4) with Mn2+ ions during 12 hours’ incubation.